THE EFFECT OF CINNAMALDEHYDE MEMBRANE APPLICATION ON THE NUMBER OF MACROPHAGES ON THE INFLAMMATION PROCESS OF LABIAL ULCUS OF WISTAR RATS - Chrisdina Puspita Sari; Nunuk Purwanti; Ika Dewi Ana (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Introduction: Macrophage is the inflammatory cell that dominates the chronic inflammation. Macrophage plays an important role in phagocytic process and secretion of chemical mediators in the early stage of inflammation. Cinnamaldehyde is the major constituent of cinnamon plant has an anti-inflammatory effect. Cinnamaldehyde can be delivered by membrane-shaped hydrogel polymer made from gelatin to maximize its anti-inflammatory effect. Aim: The objective of this study was to investigate the effect of cinnamaldehyde membrane on the macrophage numbers on the labial ulcer of Wistar rats. Methods: Thirty Wistar Rats were divided into 5 groups, 4 groups as treatment and 1 group as a control. An injury of the labial mucosa of Wistar Rat was made by the application of acetic acid glacial on the labial mucosal surface. The cinnamaldehyde membrane 1%, 4%, K-diclofenac membrane, and DMSO membrane were applied on the wound of the treatment groups, while the DMSO was applied on the control group at one day after injury. Three rats from each group were sacrificed on the 3rd and 6th day. The ulcerative mucosal tissues were collected and processed for histological preparation with Hematoksilin Eosin (HE) staining. The numbers of macrophage was counted in 6 fields using trinocular microscope. The data were analyzed using Two-way Analysis of Variance (Two-way Anova). Result: The result of Two-way Anova showed that there were significance differences between the treatment and control groups, so were the interaction of the treatment and the day. Conclusion: The application of cinnamaldehyde membrane has an effect on the numbers of macrophage on the labial ulcer of Wistar Rats.